Attitude of Senior Secondary Level Students towards Mental Illness - Nepal, S; Rayamajhi, A; Shrestha, M.; Aryal, N (Journal of Psychiatrists' Association of Nepal, 2020)
Introduction: Mental disorders are recognized as a major contributor (12%) to the global burden of disease and are among the most stigmatizing conditions worldwide. The lack of awareness is very evident in Nepal. In this study, we aimed to learn about the attitude of senior secondary level students towards mental illness. Material And Method: Descriptive cross-sectional study was conducted amongst senior secondary level students to investigate about their attitude towards mental illness. We recruited a sample of 138 students from classes 11 and 12 from a conveniently sampled school of Dharan Sub-metropolitan. Semi-structured questionnaire was used to elicit the information. Results: Our study group consisted of 53.6% females while 46.4% were males. Equal numbers of students were sampled from each grades with their ages ranging from 14-18 years. The mean for total of BMI scale was 52 and the standard deviation was observed to be 12.810. The T-tests revealed males had more negative attitude than the female students which was statistically significant with a p value of 0.048. Our study revealed that there was a significant negative correlation between the attitude scores and the grade the respondents were studying and also between the gender of the respondent, father’s and mother’s education level and in students having a family member or neighbor suffer from mental illness. Conclusion: Most of the students in the senior secondary level were found to have negative attitudes towards mental illness though no any variables were found to be contributing towards such perceptions from our research.